Effects of Training on Employee Performance in Telecommunication Industry of Nepal (Pravaha, 2020)
Employees are major assets of any organization. The vigorous role they play towards a company’s accomplishment cannot be undervalued. As a result, preparing these unique resources through effective training becomes authoritative so as to use the job performance. Also position them to require on the challenges of the today’s competitive business environment. Though general research has been shown within the area of human research management, the similar cannot be said on employee training specifically because it concerns developing nations.The purpose of this study was to gauge the consequences of training on employee performance, using the telecommunication industry in Nepal. So as to grasp the study aim, four goals were developed and these focused particularly on identifying the training programs’ current within the industry, the target of the training offered, and therefore the methods employed and lastly the results of training and development on human resource performance.The study was supported two case studies of the biggest telecommunication companies operating in Nepal. A qualitative research approach of the facts collection was approved using a questionnaire including of 18 questions dispersed to 240 respondents. Supported this sample the results found, show that training features a clear effect on the performance of employees. The findings can prove useful to human resource managers, human resource policy decision makers, still as government and academic institutions.